Corneal high-order aberrations in Fuchs endothelial corneal dystrophy and subclinical corneal edema - Blöck, Louise; Son, Hyeck Soo; Köppe, Maximilian; Friedrich, Maximilian; Auffarth, Gerd U.; Augustin, Victor A. (Cornea, 2025)
Purpose: - High-order aberrations (HOAs) are known to be increased in corneas with Fuchs endothelial dystrophy (FECD) and are associated with visual impairment. This case series aimed to analyze whether tomographic changes in FECD affect the HOA in the early period of the disease. - Methods: - In this retrospective single-center case series, 144 eyes of 85 patients were included, of which 78 eyes of 47 patients with FECD with slit-lamp biomicroscopically visible guttae but no visible corneal edema served as the study-cohort. According to Sun et al, included eyes were divided into 2 groups: group 0 (n = 28; no subclinical corneal edema) and group 1 (n = 50; subclinical corneal edema). A total of 66 healthy eyes of 38 patients served as control group. Mean values and standard deviations were calculated for the root mean square (RMS), coma, trefoil and spherical aberrations (SA) of the cornea (C), the anterior surface (CF), and the posterior surface (CB). - Results: - Statistically significant differences (P < 0.001) in the RMS HOA (group 0: 0.209 ± 0.044 μm, group 1: 0.372 ± 0.122 μm) and in coma (group 0: 0.082 ± 0.054 μm, group 1: 0.214 ± 0.101 μm) and SA (group 0: −0.130 ± 0.038 μm, group 1: −0.176 ± 0.074 μm) of the CB were found in eyes in group 1 versus those in group 0. There were no statistically significant differences in HOA between the control group and eyes in group 0. - Conclusions: - FECD eyes with subclinical corneal edema demonstrated significant increase in RMS, coma, and SA of the CB. Tomographic analysis, therefore, helps in visual impairment assessment, disease progression, and decision-making for early endothelial keratoplasty in patients with FECD.